Annual operator volume among patients treated using percutaneous coronary interventions with rotational atherectomy and procedural outcomes: Analysis based on a large national registry. Issue 6 (22nd March 2022) - Januszek, Rafał; Siudak, Zbigniew; Malinowski, Krzysztof P.; Wańha, Wojciech; Wojakowski, Wojciech; Reczuch, Krzysztof; Dobrzycki, Sławomir; Lesiak, Maciej; Hawranek, Michał; Gil, Robert J.; Witkowski, Adam; Lekston, Andrzej; et al.
Abstract: Background: Low operator and institutional volume are associated with poorer procedural and long‐term clinical outcomes in the general population of patients treated with percutaneous coronary interventions (PCI). Aim: To assess the relationship between operator experience and procedural outcomes of patients treated with PCI and rotational atherectomy (RA). Methods: Data for conducting the current analysis were obtained from the national registry of percutaneous coronary interventions (ORPKI) maintained in cooperation with the Association of Cardiovascular Interventions (AISN) of the Polish Cardiac Society. The study covers data from January 2014 to December 2020. Results: During the investigated period, there were 162 active CathLabs, at which 747, 033 PCI procedures were performed by 851 operators (377 RA operators [44.3%]). Of those, 5188 were PCI with RA procedures; average 30 ± 61 per site/7 years (Me: 3; Q1–Q3: 0–31); 6 ± 18 per operator/7 years (Me: 0; Q1–Q3: 0–3). Considering the number of RA procedures annually performed by individual operators during the analyzed 7 years, the first quartile totaled (Q1: < =2.57), the second (Q2: < =5.57), and the third (Q3: < =11.57), while the fourth quartile was (Q4: > 11.57). The maximum number of procedures was 39.86 annually per operator. We demonstrated, through a nonlinear relationship with annualized operator volume and risk‐adjusted, that operators performing more PCI with RA per year (fourth quartile) have a lower number of the overall periprocedural complications ( p = 0.019). Conclusions: High‐volume RA operators are related to lower overall periprocedural complication occurrence in patients treated with RA in comparison to low‐volume operators.